Influence of factors on the willingness to study in Lima university students - Flores Vásquez, María Elizabeth (2024)
The objective of the research was to determine the factors predicting the willingness to study among university students from a Lima-based institution. A total of 286 students aged between 24 and 29 years participated (M = 26.2, SD = 3.27), with 26.57% being male (n = 76) and 73.42% female (n = 210). Using a non-experimental, predictive causal design, measures included the Learning and Study Strategies Scale, Academic Satisfaction Scale, Family APGAR, Multidimensional Perceived Social Support Scale, and Study Willingness Scale. The results highlighted the development of a four-factor model that successfully predicted the endogenous variable at 63.4% (R2 = .652, adjusted R2 = .634, F = 77.23, p < .001). Further exploration of these factors and their practical and theoretical implications for study willingness was recommended.